Microwave-enhanced Speciation Analysis of Environmental Samples - K. Das, Arabinda; Chakraborty, Ruma (Current Microwave Chemistry, 2017)
Background: For acquiring information on accessibility, mobility, chemical behavior and fate of elements, it is necessary to determine their specific chemical species. Relevance of microwave energy for chemical speciation analysis has been extensively investigated over a wide range of applications since more than last three decades. The aim of writing this review would be to discuss salient features of important procedures applying microwave-assisted extraction followed by multi-elemental speciation through sequential extraction and speciation of several selected elements with complicated speciation chemistry. Methods: The use of microwave assisting dissolution, extraction and derivatization leads to a breakthrough in sample pretreatment for speciation analysis. After extraction, analytes were determined by atomic spectrometry such as AAS and ICP MS. A higher leaching rate could be achieved by applying focused-microwave followed by simultaneous multi-elemental detection through ICP TOFMS then that had been applied in continuous leaching followed by high resolution ICP HRMS. Results: A drastic reduction in time viz., from 68 h in the classical method to < 3.5 h in the microwave enhanced multi-elemental speciation methodology was reported and the scheme reduces the risk of contamination and involves a clean process technology. Detection limit of the order of picogram was reported for inorganic arsenic species in coal using microwave treatment followed by HPLC-HG AFS. Open focused microwave extraction using low power and less time (40-60W, 2-4 min) leads to not only reproducible and quantitative recovery but also saves the organo- mercury species intact in nanogram level. On-line non-chromatographic method for monitoring inorganic selenium species employing microwave has been found to be extremely useful for real-time speciation with picogram detection limit. Microwave-assisted extraction followed by HPLC-ES MS allows an environmentally clean method of tin speciation with femtogram detection limit. Conclusion: The use of microwave energy to prepare sample for speciation is now a necessity because tedious sample preparation procedures can not only be drastically reduced in time and simplified, but also it brings about the possibility of on-line automation. The pretreatment protocols proposed for metal species determination allow to extend the potential of these rapid sample preparation procedures to environmental matrices. Several methods have immense possibility of applying microwave-enhanced speciation in future because they are green in nature.
Keywords: selenium